2014
DOI: 10.1161/hypertensionaha.114.03300
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Protects Against Intracranial Aneurysm Rupture in Ovariectomized Mice

Abstract: Clinical observations suggest that post-menopausal women have a higher incidence of aneurysmal rupture than premenopausal women. We hypothesize that a relative deficiency in estrogen may increase the risks for aneurysmal growth and subarachnoid hemorrhage in post-menopausal women. We assessed the effects of estrogen and selective estrogen receptor subtype agonists on the development of aneurysmal rupture in ovariectomized female mice. We utilized an intracranial aneurysm mouse model that recapitulates the key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 30 publications
2
77
1
1
Order By: Relevance
“…Previous studies have shown that estrogen‐deficient rodents produce more aneurysms and that estrogen supplementation reverses this effect 5, 6, 7, 8. These previous studies do not corroborate what we observe clinically.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that estrogen‐deficient rodents produce more aneurysms and that estrogen supplementation reverses this effect 5, 6, 7, 8. These previous studies do not corroborate what we observe clinically.…”
Section: Discussioncontrasting
confidence: 99%
“…Approximately 70% to 75% of aneurysms occur in women,2 with postmenopausal women having the highest risk for aneurysm rupture 3, 4. Several studies have investigated estrogen deficiency and CA5, 6, 7, 8; however, the mechanism remains unknown. Understanding the mechanisms of aneurysms, particularly estrogen signaling, is needed to identify novel therapeutic targets.…”
mentioning
confidence: 99%
“…3 In an experimental intracranial aneurysm mouse model, estrogen prevented aneurysmal rupture in ovariectomized mice. 30 The protective effect of estrogen seemed to occur through activation of estrogen receptor-b, a predominant subtype of estrogen receptor in human intracranial aneurysms and cerebral arteries. Hormone replacement therapy (HRT) was associated with reduced risk of spontaneous SAH in postmenopausal women in most 19,22 but not all case control studies.…”
mentioning
confidence: 99%
“…Hormon estrogen juga dapat mencegah rupturnya aneurisma serebral melalui aktivasi reseptor estrogen-β yang merupakan subtipe reseptor estrogen yang dominan pada pembuluh darah otak (Tada et al, 2014).…”
Section: Metodeunclassified